Effect of using different instructional methods to teach geometry topics on fifth grade students' spatial ability and geometry achievement - Sarılıcan, Ayşegül Sanem. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2019., 2019)
The aim of this study is to investigate the eﬀects of diﬀerent instructional meth ods (technology-based, hands-on and blended instruction) to teach geometry topics on ﬁfth grade students’ spatial ability and geometry achievement. The study was conducted by using quasi-experimental pretest-posttest design. The participants of this study consisted of 57 ﬁfth grade students from three classes in a private middle school in Istanbul. Each class received one of the following methods for twenty class hours: technology-based (n=20), hands-on (n=20) and blended (n=17) instruction. In technology-based instruction, students used various geometry applications from com puters and computer tablets whereas students in hands-on instruction used concrete manipulatives. The blended instruction group used both technological and hands-on materials equally during the study. The Purdue Visualization of Rotations (ROT) Test and Diﬀerential Aptitude Test: Space Relations (DAT:SR) were used to evaluate students’ spatial ability. In order to measure students’ geometry achievement, Ge ometry Achievement Test (GAT) was developed by the researcher. The data collected from each pretest and posttest was analyzed by the nonparametric Kruskal-Wallis Test. The result of the ROT indicated a statistically signiﬁcant diﬀerence in students’ spa tial ability among the groups. Three of the instructional methods improved students’ spatial ability. However, technology-based instruction and blended instruction had sig niﬁcantly more eﬀect when compared to hands-on instruction. Furthermore, students improved their geometry achievement signiﬁcantly in each group after the treatment.
Keywords: Geometry -- Study and teaching (Elementary)